DESAIN PERKULIAHAN BAHASA INDONESIA BERBASIS HOTS (HINGER ORDER THINKING SKILLS) UNTUK MAHASISWA VOKASI - Danur Suharsono, Degita (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
Vocational education aims to prepare students who are competent in the chosen scientific discipline. As an effort to achieve this goal, the vocational student lecture system combines knowledge, skills and ethics with an emphasis on practice rather than theory. Indonesian is a general compulsory subject (MKWU) in tertiary institutions that every student must take. Vocational students need a lecture system based on Hinger Order Thinking Skills (HOTS) to improve critical, analytical and creative thinking skills as a preparation for entering the world of work. Therefore, it is necessary to develop a HOTS-based Indonesian language lecture design for vocational students. This research aims to develop an Indonesian language lecture design based on Hinger Order Thinking Skills (HOTS) for vocational students. The research method used is a development research model. This paper describes the results of product development in the form of HOTS-based Indonesian language lecture designs for vocational students. The results of this development research are in the form of a Semester Learning Plan which includes learning outcomes, learning materials, learning scenarios, and student assignment plans. Thus, the results of this development research can be used as an option for designing Indonesian language lectures for vocational students.